A Sociolinguistic Analysis of Gendered Language Features in the Movie How to Lose a Guy in 10 Days - Yosefa Isabel Namangge; Eko Setyo Humanika; Septi Riana Dewi; Ninung Pandamnurani (Lexicon, 2026)
This study aims at identifying the types of men’s and women’s language features used in the movie How to Lose a Guy in 10 Days to determine the predominant features employed by the main characters respectively based on the theories proposed by Lakoff (2004) and Coates (2013). This study adopts a descriptive qualitative method, with data collected through observation and note-taking of the characters’ dialogues in the movie. The findings reveal that the female character, Andie Anderson, uses all ten women’s language features proposed by Lakoff (2004), with lexical hedges or fillers as the most dominant (17 utterances, 25.37%). The male character, Benjamin Barry, employs all five men’s language features proposed by Coates (2013), with swearing and taboo language as the most frequent (12 utterances, 28.57%). In addition, the results show that Benjamin produces 33 utterances categorized as women’s language features, while Andie produces 8 utterances categorized as men’s language features. These results suggest that language use is flexible and influenced by communicative context rather than by gender alone.